Fine motor skills in school children diagnosed with dysarthria. A strategy for their improvement (Original) (Revista científica Olimpia, 2020)
This paper aims to provide a strategy for the improvement of fine motor skills of school children diagnosed with dysarthria. It is characterized by a system of tasks in which different plastic techniques are used. The population and the sample is constituted by four students of the Special School "Ignacio Agramonte Loynaz", which represents 100 % of the enrollment with this diagnosis in the municipality of Camagüey. In the pedagogical practice, it was found that, due to the influence of these tasks with plastic techniques, a significant contribution was made to the improvement of the fine motor skills of the students studied; hence, the proposed strategy becomes a means to promote this development.
Keywords: fine manual motor skills; schoolchildren with dysarthria diagnosis; plastic techniques